2016
DOI: 10.1016/j.ijrobp.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

What Are Medical Students in the United States Learning About Radiation Oncology? Results of a Multi-Institutional Survey

Abstract: Although MS knowledge of general RT principles improves from the first to the fourth year, a large knowledge gap still exists between MSs, current PCPs, and ROs. Some basic misconceptions of RT persist among a minority of MSs and PCPs. We recommend implementing formal education in RO fundamentals during the core curriculum of medical school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…The strategy of early integration of RO teaching may also be suitable to avoid misbeliefs in RO. A multi-institutional survey in the US showed deficiencies in knowledge concerning RO indications, toxicity, and techniques affecting first-year and fourth-year medical students [4]. An RO rotation could improve responses in all categories [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategy of early integration of RO teaching may also be suitable to avoid misbeliefs in RO. A multi-institutional survey in the US showed deficiencies in knowledge concerning RO indications, toxicity, and techniques affecting first-year and fourth-year medical students [4]. An RO rotation could improve responses in all categories [4].…”
Section: Discussionmentioning
confidence: 99%
“…With around 50% of oncological patients having an indication for radiation therapy (RT) during their course of disease [2,3], knowledge of radiation oncology (RO) has cardinal importance for both oncological disciplines as well as for general practitioners to provide patients with adequate counsel. However, there are common misbeliefs about RO and its treatment spectrum, which persist until the end of medical school [4], demanding an improvement in teaching. Innovative concepts such as internships or interdisciplinary classes could be of additional value [4,5], but are not obligatory across Germany.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty percent of countries surveyed, however, did not have dedicated radiation therapy teaching included in undergraduate medical programmes, slightly less than Australian and New Zealand exposure. In the United States of America, large knowledge gaps exist among students and a minority of respondents were found to hold basic misconceptions . A recent survey of senior medical school students in the United States revealed that only 1% had mandatory clinical experience in radiation oncology and only 30% of students had encountered a lecture in radiation oncology in their preclinical years .…”
Section: Discussionmentioning
confidence: 99%
“…In the United States of America, large knowledge gaps exist among students and a minority of respondents were found to hold basic misconceptions. 21 A recent survey of senior medical school students in the United States revealed that only 1% had mandatory clinical experience in radiation oncology and only 30% of students had encountered a lecture in radiation oncology in their preclinical years. 22 In Canada, cancer constitutes <10% of the curriculum for more than 70% of undergraduate schools 23 ; many programmes did not have a dedicated oncology curriculum.…”
Section: Discussionmentioning
confidence: 99%